Agricultural Work: Between Domestic Tasks and Professional Activities. An Approach to the role of Women in the GaruhapéColony (Misiones, Argentina) (La Rivada, 2025)
This article addresses the role and participation of women in various laborspaces in the village of Garuhapé (Misiones, Argentina) between 1940 and 1980. Using documentary sources housed in school archives and oral testimonies collectedthrough interviews, we rebuild the trajectories of women who, in addition to performing domestic tasks, became involved in agricultural production and family enterprises, as well as in teaching. Women’s laboron farms, gardens, and harvests, often rendered invisible under the category of “family help,” was fundamental to the subsistence and economic reproduction of households. However, their presence was significant, both in private-domestic and in public spaces.By becoming business owners and professional teachers, they achieved economic advancement and social recognition. Through these trajectories, the study traces women’s labourtransitions as they become active subjects evolving from mere "companions" to workers engaging in diverse fields. This research contributes to challenging androcentric historiography by recovering women's voices and trajectories from the lens ofwomen's history, and from a local perspective.
Keywords: Women; Work; Garuhapé; Local History